2021
DOI: 10.3390/biology10050377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Circuit-Based Training on Body Composition, Strength and Cardiorespiratory Fitness: A Systematic Review and Meta-Analysis

Abstract: We assessed the effects of resistance circuit-based training (CT) on strength, cardiorespiratory fitness, and body composition. A systematic review with meta-analysis was conducted in three databases, ending on March, 2020. Meta-analysis and subgroup analysis were used to analyze the effects of pre–post-intervention CT and differences from control groups (CG). Of the 830 studies found, 45 were included in the meta-analysis (58 experimental groups (n = 897) and 34 CG (n = 474)). The CT interventions led to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 72 publications
4
17
0
Order By: Relevance
“…Many guidelines for physical activity and exercise published by international associations [ 39 ] have recommended an increase in cardiovascular fitness, along with maximal strength and the improvement of body composition, to provide overall health benefits in the young [ 40 ] and elderly population [ 41 ], as well as for the improvement of quality of life in patients with different pathologies [ 42 ]. Coaches and physical educators need to take into consideration affective and motivation responses to training programs to obtain successful adherence and fulfil the recommendations made for improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many guidelines for physical activity and exercise published by international associations [ 39 ] have recommended an increase in cardiovascular fitness, along with maximal strength and the improvement of body composition, to provide overall health benefits in the young [ 40 ] and elderly population [ 41 ], as well as for the improvement of quality of life in patients with different pathologies [ 42 ]. Coaches and physical educators need to take into consideration affective and motivation responses to training programs to obtain successful adherence and fulfil the recommendations made for improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [44] and Horner et al [49] also found improvements after a RT program in VO2peak. Ramos-Campo et al [67] revealed that RT based on circuit training can positively affect cardiorespiratory fitness, namely VO2max, maximum aerobic speed or power, and aerobic performance. Furthermore, two factors have been attributed to RT producing greater EPOC.…”
Section: Discussionmentioning
confidence: 99%
“…Circuit-based resistance training is a common training method used to foster aerobic fitness, muscular endurance, and strength, as well as neuromuscular adaptations in 1 workout. Circuit-based resistance training is comprised of several sets of different exercises with little rest in between each set [ 50 ]. EX participants will be asked to return to the lab for 3 to 4 supervised sessions per week for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%